Foreign direct investment spillovers and pharmaceutical innovation: The role of intellectual property rights - Chun-Yu Ho; Xin Li; Weimin Zhou (Asian Development Bank Institute (ADBI), 2017)
This paper examines the effect of foreign direct investment (FDI) on domestic innovation based on a data set covering the pharmaceutical industries across 29 provinces in the People's Republic of China (PRC) over the period 1998-2007. We show that there is a negative horizontal spillover effect of FDI on domestic innovation when the intellectual property rights (IPR) regime is weak. This spillover effect became more positive when the IPR regime |strengthened after the PRC's accession to the World Trade Organization) (WTO) in 2001. We also show that there is a positive upstream spillover effect of FDI on domestic suppliers of pharmaceutical intermediates. Taken together, our findings provide important policy implications on why developing countries should encourage FDI and strengthen the IPR regime together to enhance domestic innovation for promoting productivity and economic growth.
Keywords: D22; F23; L65; O31; O34; O38; 330; innovation; patents; knowledge spillover; intellectual property rights; multinational enterprises; People's Republic of China